Simple treatment of ectopic eruption with a stainless steel crown - P Poornima; Sidhant Pathak; K P Bharath; K B Roopa (Wolters Kluwer Medknow Publications, 2015)
Ectopic eruption is a developmental disturbance in which the tooth fails to follow its normal eruption pathway. The purpose of this clinical report was to introduce a simple and effective way of performing ectopic eruption treatment with a stainless steel crown (SSC). In this report, the ectopic eruption case was successfully treated with SSC in 2 months. This case report demonstrates that a SSC could provide many benefits over other traditional treatment modalities and thus could be used for correcting ectopic eruption at an early age.